A systematic review and meta-analysis on herpes zoster and the risk of cardiac and cerebrovascular events. - Nathaniel Erskine; Hoang Tran; Leonard Levin; Christine Ulbricht; Joyce Fingeroth; Catarina Kiefe; Robert J Goldberg; Sonal Singh (PLoS ONE, 2017)
Patients who develop herpes zoster or herpes zoster ophthalmicus may be at risk for cerebrovascular and cardiac complications. We systematically reviewed the published literature to determine the association between herpes zoster and its subtypes with the occurrence of cerebrovascular and cardiac events.Systematic searches of PubMed (MEDLINE), SCOPUS (Embase) and Google Scholar were performed in December 2016. Eligible studies were cohort, case-control, and self-controlled case-series examining the association between herpes zoster or subtypes of herpes zoster with the occurrence of cerebrovascular and cardiac events including stroke, transient ischemic attack, coronary heart disease, and myocardial infarction. Data on the occurrence of the examined events were abstracted. Odds ratios and their accompanying confidence intervals were estimated using random and fixed effects models with statistical heterogeneity estimated with the I2 statistic. Twelve studies examining 7.9 million patients up to 28 years after the onset of herpes zoster met our pre-defined eligibility criteria. Random and fixed effects meta-analyses showed that herpes zoster, type unspecified, and herpes zoster ophthalmicus were associated with a significantly increased risk of cerebrovascular events, without any evidence of statistical heterogeneity. Our meta-analysis also found a significantly increased risk of cardiac events associated with herpes zoster, type unspecified.Our results are consistent with the accumulating body of evidence that herpes zoster and herpes zoster ophthalmicus are significantly associated with cerebrovascular and cardiovascular events.